Equal treatment for highly qualified labour migrants - Petra Herzfeld Olsson (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2019)
According to EU-law, third country national labour migrants shall be treated equally to local workers with regard to wages. The aim of this working paper is to clarify whether Swedish law meets this demand with regard to highly qualified labour migrants. The analysis reveals that the combined effect of entry conditions and the content of the collective agreements applicable in the sectors where highly qualified labour migrants work makes it difficult to safeguard that they are treated equally with comparable national workers. The study also demonstrates that Swedish law does not provide highly qualified labour migrants with any robust means to enforce equal treatment. Hence, it is not likely that Swedish law complies with EU law, at least not for those workers employed by an entity in Sweden. For labour migrants intra-corporate transferred or posted to Sweden in other ways the EU law demands are less clear.
Keywords: J31; J61; J71; J83; K31; K37; K38; 330; Highly qualified labour migrants; pay; collective agreements; equal treatment